Gliflozins position update in the treatment algorithms for patients with type 2 diabetes mellitus and chronic kidney disease: new pathogenetic mechanisms and data from subanalyses of the large randomised control trails - O. Y. Sukhareva; Z. T. Zuraeva; M. S. Shamhalova (Сахарный диабет)
The series of the cardiovascular outcome trails have demonstrated the nephroprotective properties of the gliflozins. Canagliflozin in the CREDENCE, which was the first study with a primary focus on the evaluation of the nephroprotective properties of gliflozin, have demonstrated the possibility to slow the progression of the renal disease. The paper summarizes the additional data from the CREDENCE trail: assessment of the efficacy of canagliflozin by initial eGFR; efficacy in individuals with GFR <30 ml/min/1.73 m2 ; long-term effects of canagliflozin on anaemia-related outcomes; effects of canagliflozin on serum potassium; effects on heart failure and cardiovascular mortality. There are discussed the current treatment algorithms for patients with type 2 diabetes and CKD where using of gliflozins is a priority option. Canagliflozin is a drug with a relatively low ratio of SGLT1/SGLT2 selectivity. The effects of the inhibition of SGLT1 transport in the kidney and in the intestine are described and their additional influence on reducing of the postprandial glycemia and additional nephroprotection.